Designing a Geo-Edu Park through Structural Landform Analysis: Insights from Teletubbies Hill, Indonesia - Darmawangsa, Wahyu Ramadhan; Widagdo, Arif Surya; Lapian, Gianangel Emmanuela; Pangestu, Farizki Budi; Pintrandhita, Anwar Said (Centre for Tourism Studies and Journal Publication of Sekolah Tinggi Pariwisata Mataram, 2024)
This study explores the geotourism potential of Teletubbies Hill in Wukirharjo Village, Yogyakarta, through detailed topographical and geomorphological mapping. Employing a terrestrial survey method using Total Station instruments, the research generates high-resolution elevation data to assess landforms and slopes shaped by ancient volcanic processes associated with the Semilir Supervolcano. Morphographic and morphometric analyses reveal that the site consists of structural hills with slopes ranging from 8% to 20%, categorized into two development zones based on slope steepness. The findings support the suitability of Teletubbies Hill for sustainable geotourism initiatives that combine education, recreation, and conservation. Proposed developments include the construction of a geological museum and an outdoor geological park to highlight the region's volcanic heritage and geological features. This integrated approach offers a framework for transforming underutilized landscapes into educational geotourism destinations. While the reliance on terrestrial methods limits broader geological context, future research could incorporate remote sensing and socio-economic feasibility assessments to enhance planning outcomes.